Begæret, volden og offeret - Frandsen, Finn (Religionsvidenskabeligt Tidsskrift, 1985)
The French critic and anthropologist René Girard is one of the most original and controversial thinkers of today. This article contains an introduction to his theory of the unanimous victimage as the generative mechanism of all religious and social institutions. The main element in this mechanism is the mimetic desire, i.e. a desire which depends on a mediator and whose dynamics is rooted in a dispute object. Every human society has originally known a state of crisis caused by mimetic rivalry and contagious, reciprocal violence. The function of the victimage mechanism is to stop the crisis, to institute a cultural order based on differences and hierarchy, and to reconcile the members of the community by expelling and sacrificing one single person considered to be the cause of the evil. The purpose of prohibitions, rituals and myths is afterwards to maintain and renew this reconciling “scapegoat effect”. The introduction also includes two shorter chapters on René Girard’s interpretation of the Oedipus myth and his non-sacrificial reading of the evangelic text.